Association between vitamin D deficiency and psoriasis: An exploratory study - Al-Dhubaibi, Mohammed Saleh (International Journal of Health Sciences, 2018)
Deficiency of Vitamin D is a widespread problem. Vitamin D could have important immune modulatory effects in psoriasis. Objective: Aimed to review and endeavoured to establish the relationship, if any, between deficiency of Vitamin D and Psoriasis. Methods: Leading studies that examined the relationship between deficiency of vitamin D and Psoriasis were reviewed from July2016 to October 2016. An electronic published work search was performed using PubMed, Ovid MEDLINE, Google Scholar and Saudi Digital Library. Results: A total of 2132 eligible articles were identified by the electronic search. The titles and abstracts of 954 articles fulfilled the criteria of midline search. Twenty articles were included after application of inclusion standards and full-text review. These 20 studies included 2046 psoriatic patients with or without arthritis and 6508 healthy controls. Fourteen studies show a positive correlation between vitamin D deficiency and psoriasis. These 14 studies included 1249 psoriatic patients with or without arthritis and 680 healthy controls. Remaining six studies, including 797 psoriatic patients with or without arthritis and 5828 healthy controls do not depict a positive correlation between the two variables under study. Conclusion: There exists a correlation of psoriasis with deficiency of Vitamin D. However, there is a need for larger scale case-control studies to assess how far vitamin D deficiency plays a role in psoriasis.